2016
DOI: 10.1121/1.4968530
|View full text |Cite
|
Sign up to set email alerts
|

Noise control zone for a periodic ducted Helmholtz resonator system

Abstract: This paper presents a theoretical study of the dispersion characteristics of sound wave propagation in a periodic ducted Helmholtz resonator (HR) system. The predicted result fits well with a numerical simulation using a finite element method. This study indicates that for the same system, no matter how many HRs are connected or what the periodic distance is, the area under average transmission loss T L¯ curves is always the same. The broader the noise attenuation band, the lower the peak attenuation amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…While passive interference is known to alter the acoustic performance, the challenge for this research is to investigate the possibility of designing an acoustic absorber that utilises interference for passive destruction and not in the commonly used active form. The benefit of this approach is the increased design flexibility that allows for free-form designs as compared to commonly used resonance approaches such as quarter-wave [50] or Helmholtz resonators [51]. As can be seen, the proposed system dismisses the requirement for acoustical signal monitoring or generation as featured in active systems.…”
Section: The Principle Behind the Proposed Design-based Interferencementioning
confidence: 99%
“…While passive interference is known to alter the acoustic performance, the challenge for this research is to investigate the possibility of designing an acoustic absorber that utilises interference for passive destruction and not in the commonly used active form. The benefit of this approach is the increased design flexibility that allows for free-form designs as compared to commonly used resonance approaches such as quarter-wave [50] or Helmholtz resonators [51]. As can be seen, the proposed system dismisses the requirement for acoustical signal monitoring or generation as featured in active systems.…”
Section: The Principle Behind the Proposed Design-based Interferencementioning
confidence: 99%
“…However, the noise attenuation capacity of every single HR in the system remains unchanged [14]. The transmission loss of the whole system is fairly dependent on the number of HRs.…”
Section: Theoretical Analysis Of a Helmholtz Resonator Array Consimentioning
confidence: 99%
“…Wang and Mak [13] investigated the wave propagation in a duct mounted with an array of identical resonators and presented theoretical methods of noise attenuation bandwidth prediction. Cai and Mak [14] proposed a noise control zone comprising the attenuation bandwidth or peak amplitude of a periodically ducted HR system. Their results indicated that the broader the noise attenuation band, the lower the peak attenuation amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…The other utilizes the coupling effects of the resonator and the structure to achieve broadband noise attenuation. The wave propagation in a periodic structure exhibits peculiar characteristics results from the Bragg reflections [15][16] . Owing to the coupling of the periodic structure and the resonator, the resonators distributed periodically on the duct provide a much broader noise attenuation compared to a single resonator 17) .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a broader noise attenuation band, combining several resonators in line is a possible way. Numerous studies have been conducted following this idea using two methods [12][13][14][15][16][17][18][19][20] . One uses a serial arrangement of resonators with different resonance frequencies to obtain a wide band of noise control in ducts.…”
Section: Introductionmentioning
confidence: 99%